2015
DOI: 10.1371/journal.pone.0128755
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Significance of Chiral Genitalia: Patterns of Asymmetry, Functional Morphology and Mating Success in the Praying Mantis Ciulfina baldersoni

Abstract: Genital asymmetry is relatively common and widespread throughout the animal kingdom. The functional significance of genital asymmetry is however, poorly understood for most species. Male praying mantids of the genus Ciulfina are remarkable in possessing complex and directionally asymmetric genital phallomeres in some species, and chirally dimorphic/antisymmetric genitalia in others. Here we explore the chiral dimorphism in male genitalia of Ciulfina baldersoni which appear to exhibit genital antisymmetry. We t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The normal (dextral) orientation of the phallic asymmetry is as in Figs 10–11, 13 (see also Klass 1997: figs 3, 24, 31, 38). However, a few mantodean genera (e.g., Ciulfina Giglio-Tos, 1915, Haania Saussure, 1871) include species with a side-reversed asymmetry, i.e., the phallic organs are mirror-imaged compared to those of other mantodeans (sinistral orientation), or species where both dextral and sinistral males occur (e.g., Balderson 1978, Anisyutkin and Gorochov 2004, Holwell et al 2007, 2015). In cases of a sinistral orientation, the terms for left and right structures of the phallic organs must also be applied in a side-reversed way.…”
Section: Resultsmentioning
confidence: 99%
“…The normal (dextral) orientation of the phallic asymmetry is as in Figs 10–11, 13 (see also Klass 1997: figs 3, 24, 31, 38). However, a few mantodean genera (e.g., Ciulfina Giglio-Tos, 1915, Haania Saussure, 1871) include species with a side-reversed asymmetry, i.e., the phallic organs are mirror-imaged compared to those of other mantodeans (sinistral orientation), or species where both dextral and sinistral males occur (e.g., Balderson 1978, Anisyutkin and Gorochov 2004, Holwell et al 2007, 2015). In cases of a sinistral orientation, the terms for left and right structures of the phallic organs must also be applied in a side-reversed way.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, males approaching them from another side will have an advantage. However, to our knowledge, no study has demonstrated this type of frequency‐dependent selection for insect courtship behaviour and genital interactions (but see Holwell, Kazakova, Evans, O'Hanlon, & Barry (), for a possible case).…”
Section: Discussionmentioning
confidence: 98%
“…Male mantises have genitalia consisting of three phallic parts, the dorsal and ventral components of the left coplex and the right phallomere (Holwell et al. ; fig. ).…”
Section: Introductionmentioning
confidence: 99%
“…The male twists his abdomen one way or the other; sinistral males twist to the left and dextral to the right (Holwell et al. ). Such male‐dominated positions require abdominal twisting, flexing and asymmetric contact between male and female genitalia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation